Investigation of AISI 904L austenitic stainless steel by carbonitriding process under dry sliding conditions. (2021) - Koppula, Shivani; Gautam Jagarlamudi, Venkata; Sai Prudhvi, Reddi; Rajkumar, Aakula; Prashanth, S.; Saranya, J.; Sateesh, N.; Subbiah, Ram
Abstract: The austenitic stainless steel AISI 904L is remarkable for its disintegration restriction, fitting to high pitting and stress hindrance. The materials to improve the wear lead of the material. Carbonitriding treatment is picked to help the mechanical properties of AISI 904L austenitic stainless steel. The models experience carbonitriding treatment, at low temperatures, one of them being honoured to get quite far. For assessment reasons, one model is kept as untreated. A pin on circle wear testing gadget will be aimed at a steady speed and variable weight. Wear test is done to assess the capacity of utilizing a specific surface structure headway to decrease wear for a particular application and to examine the impact of treatment conditions on the wear execution, so updated surface treatment conditions can understand it. At long last, all models were knowledgeable about Scanning Electron Microscope assessment.